Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1093/ptj/83.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Voluntary and Functional Performance Needed for Independence in Adults Aged 65 to 97 Years

Abstract: Background and Purpose. Age-related loss of muscle mass and cardiovascular endurance can lead to impairments in muscle force production and cardiac function that, in turn, limit performance in activities essential to everyday living. The purposes of this study were: (1) to identify the “breakpoint” or threshold of maximal voluntary performance and performance in ordinary daily function (2) to evaluate the predictive validity of the threshold to identify the ability independently without self-reported functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(78 citation statements)
references
References 37 publications
4
68
1
3
Order By: Relevance
“…Thus, in terms of lower limb muscle strength and power, the present findings suggest the existence of a substantial physical reserve among healthy older individuals, whereby lower single-limb strength/power levels (and/or potential inter-limb asymmetries herein) may remain beyond any critical threshold below which it would start to negatively affect physical function. 11 Supporting the present observations, LaRoche and colleagues 14 also reported the weakest leg to not be a better predictor of functional performance than the stronger leg in community-dwelling older adults at risk of mobility limitation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, in terms of lower limb muscle strength and power, the present findings suggest the existence of a substantial physical reserve among healthy older individuals, whereby lower single-limb strength/power levels (and/or potential inter-limb asymmetries herein) may remain beyond any critical threshold below which it would start to negatively affect physical function. 11 Supporting the present observations, LaRoche and colleagues 14 also reported the weakest leg to not be a better predictor of functional performance than the stronger leg in community-dwelling older adults at risk of mobility limitation.…”
Section: Discussionsupporting
confidence: 81%
“…6,10 However, in well-functioning older individuals, the initial loss of muscle strength and power may not have strong impact on functional capacity, as the relationship between muscle strength/power and functional capability appears to be plateauing (ie, reach a ceiling region) at the upper end of this relationship. 11 A vast number of physical activities of daily living (ADL) involve bilateral lower limb movements (walking, chair stand, stair climbing, etc), and the ability to perform these activities will therefore be limited by bilateral lower limb muscle function. Thus, another possible determinant of functional capacity could be the degree of lower limb asymmetry in the aforementioned factors.…”
mentioning
confidence: 99%
“…26 The United States Social Security Administration (SSA) has identified a peak VO 2 below 18.0 mL O 2 /kg per minute as indicating disability, 27 and several empirical studies of older adults have found similar threshold values for independent living. [3][4][5]21 Substituting the study population mean value for ending SBP (174 mmHg) in the estimating equation and using the SSA criteria equates to a 400-m time of 4 minutes 57 seconds for short stride and 5 minutes 49 seconds for long stride. Applying Astrand's estimate of 12 mL O 2 /kg per minute as the minimum requirement for walking across a street 5 translates to a 400-m time ranging from 6 minutes 48 seconds to 7 minutes 40 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…21 Other measures of muscle strength included isokinetic knee extension torque and knee extension strength; however, these are not used as frequently (cut-off values summarized in Table 1). 40,41,48,51…”
Section: Muscle Strengthmentioning
confidence: 99%